Prawo administracyjne jako narzędzie przeciwdziałania korupcji funkcjonariuszy administracji publicznej - Kozłowska, Małgorzata Klaudia (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
Public administration is highly affected by the corruption. A research conducted in this respect shows that the root cause of the corruption is the latter – a human, an official whose behaviour accepts or provokes the procedure. Several areas of prevention addressed to public administration officials have been distinguished, namely: 1. Limitation of business activity, 2. Compulsory submission of property statements, 3. Restrictions with starting additional business activity, including economic activity and combination of positions and mandates, 4. Ban on combining positions, functions and mandates, 5. Ensuring transparency at work in public administration.
Keywords: administrative law; corruption; public administration officials